Education for social change : perspectives on global learning - Bourn, Douglas (London, England : Zed Books, 2022)
"This book introduces students to education as a vehicle for social change. Douglas Bourn begins by providing historical context of how education has been linked to social change around the world and moves on, in the second section of the book, to discuss potential theoretical and conceptual frameworks for thinking about education for social change. The third sections covers how social change has been explored and promoted within different areas of learning, including schooling, youth work and higher education. The fourth section looks at the opportunities and challenges for promoting education for social change and reviews current international initiatives including those of global citizenship and climate change. Key theorists are introduced throughout the book including bell hooks, Dewey, Giroux, Gramsci, and Freire. Each chapter begins with an opening question and ends with bulleted concluding points, questions for discussion and a further reading list. The book includes a foreword written by Tania Ramalho (State University of New York, USA)."--
List of Figures -- Foreword, Tania Ramalho (State University of New York, USA) -- Acknowledgements -- List of Abbreviations -- Introduction -- 1. Changing Role and Relationship of Education to Societal Change -- 2. Education for a Democratic Society -- 3. Education for Liberation -- 4. Education for Socialism and a New Society -- 5. Education for a Global Society -- 6. Pedagogy for Global Social Justice -- 7. Education for Transformation, Sustainable Future and Being Global Citizens -- 8. Teachers as Agents of Social Change -- 9. Global Youth Work and Young People as Social Activists -- 10. The Role of the Academic Tutor -- 11. Civil Society Organisations as Agents for Change -- 12. International Organisations, UNESCO, Earth Charter and Putting the Sustainable Development Goals into Practice -- Conclusion -- References -- Index
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Education -- Social aspects -- Cross-cultural studies; Education -- Social aspects; Philosophy & theory of education; Electronic books